Answer:
x= 1
Explanation:
Convert 5\frac{11}{12}5
12
11
to improper fraction. Use this rule: a \frac{b}{c}=\frac{ac+b}{c}a
c
b
=
c
ac+b
3.25+0.5x+1\frac{1}{3}+\frac{5}{6}x=\frac{5\times 12+11}{12}3.25+0.5x+1
3
1
+
6
5
x=
12
5×12+11
2 Simplify 5\times 125×12 to 6060
3.25+0.5x+1\frac{1}{3}+\frac{5}{6}x=\frac{60+11}{12}3.25+0.5x+1
3
1
+
6
5
x=
12
60+11
3 Simplify 60+1160+11 to 7171
3.25+0.5x+1\frac{1}{3}+\frac{5}{6}x=\frac{71}{12}3.25+0.5x+1
3
1
+
6
5
x=
12
71
4 Simplify \frac{5}{6}x
6
5
x to \frac{5x}{6}
6
5x
3.25+0.5x+1\frac{1}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+1
3
1
+
6
5x
=
12
71
5 Convert 1\frac{1}{3}1
3
1
to improper fraction. Use this rule: a \frac{b}{c}=\frac{ac+b}{c}a
c
b
=
c
ac+b
3.25+0.5x+\frac{1\times 3+1}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+
3
1×3+1
+
6
5x
=
12
71
6 Simplify 1\times 31×3 to 33
3.25+0.5x+\frac{3+1}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+
3
3+1
+
6
5x
=
12
71
7 Simplify 3+13+1 to 44
3.25+0.5x+\frac{4}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+
3
4
+
6
5x
=
12
71
8 Simplify 3.25+0.5x+\frac{4}{3}+\frac{5x}{6}3.25+0.5x+
3
4
+
6
5x
to \frac{13.75}{3}+\frac{4x}{3}
3
13.75
+
3
4x
\frac{13.75}{3}+\frac{4x}{3}=\frac{71}{12}
3
13.75
+
3
4x
=
12
71
9 Simplify \frac{13.75}{3}
3
13.75
to 4.5833334.583333
4.583333+\frac{4x}{3}=\frac{71}{12}4.583333+
3
4x
=
12
71
10 Subtract 4.5833334.583333 from both sides
\frac{4x}{3}=\frac{71}{12}-4.583333
3
4x
=
12
71
−4.583333
11 Simplify \frac{71}{12}-4.583333
12
71
−4.583333 to \frac{4}{3}
3
4
\frac{4x}{3}=\frac{4}{3}
3
4x
=
3
4
12 Multiply both sides by 33
4x=\frac{4}{3}\times 34x=
3
4
×3
13 Simplify \frac{4}{3}\times 3
3
4
×3 to \frac{12}{3}
3
12
4x=\frac{12}{3}4x=
3
12
14 Simplify \frac{12}{3}
3
12
to 44
4x=44x=4
15 Divide both sides by 44
x=1